Al-Islām al-Mu’tadil wa Thaqāfat Bangka Belitung: Al-Manẓūrat al-Antrūbūlūjīyah - Zulkifli, Zulkifli (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2010)
This article explains moderate Islam in Bangka-Belitung culture from anthropological perspective. This article defines moderate Islam as in line with moderateness, compromises with a spirit to reject all forms of violence. Moderate Islam is the true character of Islam, because moderate Islam believes that Islam brings peace. Due to the limited studies in the form of anthropology, politics, economics, and history on Bangka-Belitung community, this article relies on limited sources. Thus, this article is based on personal observation and experience as an insider. Although it cannot escape from many shortcomings, insider observation has become one of the strategies to enrich this study and to understand the nuances of the holistic nature of this study.DOI: 10.15408/sdi.v17i3.458